JURISDICTION IN CIVIL PROCEDURAL LAW, SOME PROBLEMS IN PRACTICE AND FOREIGN ANALYSIS - Egamberdiyev, D. (International Journal of Psychosocial Rehabilitation, 2020)
The reforms carried out in the context of modernization and reform of the country in the judicial and legal sphere are aimed primarily at the comprehensive protection of human rights, freedoms and legitimate interests. Over the past period, large-scale organizational and legal measures aimed at gradually strengthening the judiciary, ensuring the independence of the court, reliable protection of human and civil rights and freedoms have been implemented. Currently, the courts also have problems related to jurisdiction. In this article the analysis of judicial jurisdiction in civil procedural law, some problems in practice and foreign countries is carried out. Today, this problem in practice causes problems for both judges and citizens. This article is devoted to these issues.